2023
DOI: 10.1177/17588359231156870
|View full text |Cite
|
Sign up to set email alerts
|

Future therapeutic strategies in the treatment of extrapulmonary neuroendocrine carcinoma: a review

Abstract: Neuroendocrine neoplasms (NENs) are rare malignancies arising most commonly in the gastrointestinal and bronchopulmonary systems. Neuroendocrine carcinomas (NECs) are a subgroup of NENs characterised by aggressive tumour biology, poor differentiation and dismal prognosis. Most NEC primary lesions arise in the pulmonary system. However, a small proportion arise outside of the lung and are termed extrapulmonary (EP)-, poorly differentiated (PD)-NECs. Patients with local or locoregional disease may benefit from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…The small sample size and retrospective design of the study hinder reliable conclusions. The NEONEC trial is currently investigating the activity of adjuvant platinum-based chemotherapy in patients who underwent surgery for digestive NECs, and the results are eagerly awaited (NCT04268121) [8].…”
Section: Management Of Gep-necsmentioning
confidence: 99%
See 2 more Smart Citations
“…The small sample size and retrospective design of the study hinder reliable conclusions. The NEONEC trial is currently investigating the activity of adjuvant platinum-based chemotherapy in patients who underwent surgery for digestive NECs, and the results are eagerly awaited (NCT04268121) [8].…”
Section: Management Of Gep-necsmentioning
confidence: 99%
“…On the other hand, single-agent pembrolizumab, another PD-1 inhibitor, failed to improve survival in an unselected population enrolled in a small phase II trial [97,101]. Given the interest in investigating the efficacy of ICIs, especially for the novel PD-(L)1-CTLA-4 dual inhibitors, a phase II trial of cadonilimab, a bispecific anti-PD-1/CTLA-4 inhibitor, is ongoing for the second-and third-line setting in recurrent NECs of the cervix (NCT05063916) [8,102].…”
Section: Necs Of the Cervixmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PD-L1 expression appears quite heterogeneous across different studies[ 57 ], even though some studies revealed no relevance between the effectiveness of ICIs and PD-L1 expression[ 30 , 31 , 40 ]. Reasons for these results may be subject to limitations due to factors such as different methods of analysis, defined cutoffs, and the freshness of biopsy tissue obtained[ 58 ]. Therefore, based on identifying the expression of PD-L1, investigate the content of other predictive biomarkers to provide patients with the best immunotherapy prediction possible.…”
Section: Biomarkers For Predicting Immunotherapy Responsementioning
confidence: 99%
“…Lymphadenectomy is suggested to be performed with surgical resection if suspected lymph nodes metastasis exist [3,27]. Platinum-based chemotherapy with etoposide and cisplatin is the first-line treatment for NECs, while irinotecan and cisplatin are found to be not inferior to etoposide and cisplatin [28][29][30][31][32]. Radiotherapy is commonly used as the secondline treatment of NETs.…”
Section: Introductionmentioning
confidence: 99%